Caracterización normativa y contable de las parroquias de la diócesis de Duitama – Sogamoso (2022)
In this research, it analyzes the historical recognition, the sources of money for the legal entities of ESALs, bearing in mind that they are non-profit entities, with civil recognition, responsibilities and privileges that are currently recognized, since the concordat with the Holy Headquarters and the Colombian State, arriving at not being clear about how the management of financial information is compared to the accounting standard of the parishes of the Duitama - Sogamoso diocese; it proposes to have an approach in characterizing the management of financial information according to the normative parameters (such norm) in the parishes of the Duitama – Sogamoso diocese; within the stages we have, the identification of the accounting policy related to the ecclesial part starting from history, conducting interviews with people immersed in the subject in order to know the internal policies of the accounting economy of the Diocese; another stage in which the accounting regulations for income and its application in the current demands of the parishes is verified and the third is to evaluate the recognition and measurement of the income of the parishes of the Diocese of Duitama - Sogamoso, thus generating a primer that be in simple but technical language, carrying the current regulations for the parishes and that it be practical for their legal representatives; Through this work it can be concluded that the lack of knowledge of the parish accounting issue in our training will be of great help to our profession of accountants, as well as for the updating of accounting requirements for each of the parishes, of great public interest clarifying for the faithful the financial information and what is the true destination of the income of the parishes.